Buddhism: Rise and Fall in India in Confrontation with Hinduism - Kochumuttom, Thomas (Journal of Dharma, 1995)
Generally speaking Buddhism has a fascinating history of giveand-take with the other religions and cultures. Christianity and Buddhism after a small beginning spread rapidly, one to the West and the other to the East. Christianity spread to the West rather imposing itself on others, by trying either to destroy or replace other religions and cultures, while Buddhism spread to the East by enriching other religions and cultures, and by being enriched by them. Wherever it went. nobly assimilating the religions and cultural insights of that place, Buddhism took a new form, and gently inspired the local religions and cultures to imbibe the Buddhist spirit. The result is that just as by the influence of Christianity the Western culture has become a basically Christian one, so by the influence of Buddhism the Eastern culture has become a basically Buddhist one. All the same there is one important difference indeed: while the previously existing cultures and religions in the West simply gave way to Christianity, and the latter took their place, in the East the encounter of Buddhism with the other religions and cultures resulted in a creative transformation of Buddhism itself as well as of those others. Buddhism, not insisting on uniformity, easily took on different forms in accordance with the religious and cultural ethos of the different regions, while the original religions and cultures of those places allowed themselves to be influenced by the Buddhist ethos. This is the story of the different forms of Buddhism in Tibet, China, Japan, Burma, Sri Lanka, India and so on. While all of them retain ,he basically Buddhist perception of life, they also differ considerably from one another, having transformed in accordance with the particular ethos of each of those countries.